Obesity and risk of colorectal cancer: a systematic review of prospective studies. - Yanlei Ma (Public Library of Science (PLoS), 2013)
Background Mounting evidence indicates that obesity may be associated with the risk of colorectal cancer (CRC). To conduct a systematic review of prospective studies assessing the association of obesity with the risk of CRC using meta-analysis. Methodology/principal findings Relevant studies were identified by a search of MEDLINE and EMBASE databases before January 2012, with no restrictions. We also reviewed reference lists from retrieved articles. We included prospective studies that reported relative risk (RR) estimates with 95% confidence intervals (CIs) for the association between general obesity [measured using body mass index (BMI)] or central obesity [measured using waist circumference (WC)] and the risk of colorectal, colon, or rectal cancer. Approximately 9, 000, 000 participants from several countries were included in this analysis. 41 studies on general obesity and 13 studies on central obesity were included in the meta-analysis. The pooled RRs of CRC for the obese vs. normal category of BMI were 1.334 (95% CI, 1.253-1.420), and the highest vs. lowest category of WC were 1.455 (95% CI, 1.327-1.596). There was heterogeneity among studies of BMI (P<0.001) but not among studies of WC (P=0.323). Conclusions Both of general and central obesity were positively associated with the risk of CRC in this meta-analysis.